Principles of teaching and instructional technology - Navarro, Rosita L.; Cruz, Amelita A.; Tovera, David G.; Lucido, Paz I. (Quezon City : Philippines Association for Teacher Education and Katha Publishing Co., Inc., 1988)
The book principles of teaching and instructional technology is the product of the cooperative effort to bring together, as in a compendium, all the important principles of teaching that prospective teachers need to know, including the more current ones which have emerged with the advent of technology.
Part I. Basic Principles of teaching -- Chapter I. The Teacher and The Teaching process -- Chapter II. The Teaching Cycle -- Part II. Instructional management and curriculum management -- Chapter III. Taxonomy of educational objectives -- Chapter IV. The Curriculum -- Part III. The Role of media technology in education -- Chapter V. The Theoretical basis of media technology -- Chapter VI. Planning and Producing media materials -- Chapter VII. The Computer as an aid to teaching -- Chapter VIII. Teaching with the computer.
Includes bibliographical references.
Keywords: EDUCATIONAL TECHNOLOGY; TEACHING